2011
DOI: 10.1210/en.2011-0045
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Bisphenol A at Reference Dose Predisposes Offspring to Metabolic Syndrome in Adult Rats on a High-Fat Diet

Abstract: Bisphenol A (BPA), a widely used environmental endocrine disruptor, has been reported to disrupt glucose homeostasis. BPA exposure may be a risk factor for type 2 diabetes. In this study, we investigated the effects of early-life BPA exposure on metabolic syndrome in rat offspring fed a normal diet and a high-fat diet. Pregnant Wistar rats were exposed to BPA (50, 250, or 1250 μg/kg · d) or corn oil throughout gestation and lactation by oral gavage. Offspring were fed a normal diet or a high-fat diet after wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
187
4
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 267 publications
(227 citation statements)
references
References 49 publications
27
187
4
9
Order By: Relevance
“…In the present study, we first demonstrated that long-term oral exposure to BPA induced glucose intolerance after the neonatal period by increasing insulin resistance in a manner that was not related to b cell dysfunction. These findings are consistent with previously published epidemiologic data (Lang et al 2008, Shankar & Teppala 2011, Wang et al 2012 and animal studies (Alonso-Magdalena et al 2006, Wei et al 2011, Batista et al 2012). In two large epidemiologic studies, urinary BPA level was positively associated with type 2 diabetes mellitus (Shankar & Teppala 2011) and with obesity and insulin resistance (Wang et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we first demonstrated that long-term oral exposure to BPA induced glucose intolerance after the neonatal period by increasing insulin resistance in a manner that was not related to b cell dysfunction. These findings are consistent with previously published epidemiologic data (Lang et al 2008, Shankar & Teppala 2011, Wang et al 2012 and animal studies (Alonso-Magdalena et al 2006, Wei et al 2011, Batista et al 2012). In two large epidemiologic studies, urinary BPA level was positively associated with type 2 diabetes mellitus (Shankar & Teppala 2011) and with obesity and insulin resistance (Wang et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In the past decades, EDCs have been recognized to exhibit a lack of linear dose-dependent relationship with endocrine abnormalities, showing instead inverted U-shaped curves (Alonso-Magdalena et al 2011). In a recent report from Wei et al (2011), perinatal exposure to BPA (50 mg/kg per day) induces hyperinsulinemia and impaired glucose regulation in SD rat offspring. Interestingly, the effects are not observed at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in rodents indicated that BPA directly affects pancreatic b-cell functions (Alonso-Magdalena et al 2010, Wei et al 2011), and a recent paper has demonstrated in a rat insulinoma cell line that BPA affects pancreatic function on insulin production by decreasing insulin production and secretion (Lin et al 2013).…”
Section: Bpa Regulates Insulin Productionmentioning
confidence: 97%